Factors that influence the effectiveness of leadership training program : a study case at Jabatan Pengangkutan Jalan (JPJ) negeri Sabah, Kota Kinabalu - Merda @ Ida Lojimin, @ Richard (Universiti Malaysia Sarawak, (UNIMAS), 2005)
This study aims to identify the factors that influence the effectiveness of leadership-training program at Jabatan Pengangkutan Jalan (JPJ) Negeri Sabah, Kota Kinabalu. The independent variables that had been examined were factor of selected demography such as respondents' age, educational level, work experience, and also the factor of trainer's presentation style, factor of motivation and factor of training environment meanwhile the dependent variable was the effectiveness of leadership-training program. There are 39 respondents involved in this study that are consist of employees in Jabatan Pengangkutan Jalan (JPJ) Negeri Sabah, Kota Kinabalu, and those who had been attended the leadership-training program. Instrument used for this study is questionnaire. The questionnaire is reliable at alpha coefficient value of 'r' = 0.8339. The descriptive statistical used the frequency and percentage to analyze data, and inferential statistical involved the One-way of Variance (ANOVA) and the Pearson Correlation Coefficient 'r'. The overall findings showed that the factor of motivation is the most affecting factors that influence the effectiveness of leadership-training program in Jabatan Pengangkutan Jalan (JPJ) Negeri Sabah, Kota Kinabalu. Besides that, the researcher also found that majority of the respondents which are 97.4% (n = 38) rated the leadership-training program as an effective training program while there only 2.6% (n = 1) of the respondents rated the training program as less effective. The result findings of this study might be useful to the organization in improving and establishing the execution of the leadership-training program among the employees.